Exploring EFL Students’ Experiences of Islamic Value-Concordant Learning through the Lens of Self-Determination Theory - Zulfah Fakhruddin; Kalsum; Karmila Jamal (Universitas Islam Negeri Palopo, 2025)
This study aims to describe the levels of psychological satisfaction and frustration specifically autonomy, competence, and relatedness experienced by 200 EFL students from the Faculty of Tarbiyah at IAIN Parepare within faith-based English learning environments. Using a quantitative survey method, data were collected through a structured questionnaire and analyzed using descriptive statistics. The results revealed a moderate level of satisfaction (M = 3.69) and a low level of frustration (M = 2.31), indicating that students’ basic psychological needs were generally well supported. High satisfaction was found in autonomy and relatedness, suggesting that students felt respected, connected, and free to express themselves within a context that integrates Islamic values such as ṣidq (honesty), amānah (responsibility), and raḥmah (compassion). Meanwhile, competence remained moderate, implying that some learners continued to face challenges in achieving language mastery. These findings suggest that Islamic value-concordant learning characterized by the integration of moral, spiritual, and cultural principles of Islam into language teaching can enhance students’ motivation, social bonds, and emotional well-being while reducing anxiety and pressure. The novelty of this study lies in applying Self-Determination Theory (SDT) within an Islamic higher education context to explore how faith-aligned pedagogy supports psychological needs. However, this research is limited to one institution; future studies could adopt a comparative or longitudinal design to deepen understanding. In conclusion, integrating Islamic values into English language learning not only strengthens students’ linguistic and academic outcomes but also nurtures psychological fulfilment and spiritual growth, making it a holistic approach to education.